Characterizing Spray Propagation of GDI Injectors under Crossflow Conditions - Welß, Richard; Bornschlegel, Sebastian; Wensing, Michael (SAE Technical Papers, 2018)
In DISI engines spray distribution and atomization directly influence mixture formation, the quality of combustion and the resulting emissions. Constant Volume Chambers (CVC) are commonly used to characterize sprays of gasoline injectors. The CVCs provide good optical access but the flow condition of the engine cannot be reproduced. Optically accessible engines in contrast deliver realistic flow conditions but have restricted optical access. In former investigations we compared the spray propagation of different injectors in constant volume chambers and in optical accessible engines. These results showed a clear difference of the spray propagation in the CVC and the engine, especially at high charge motion conditions in the engine. To find an appropriate way to investigate the impact of different charge motion a flow channel was built with adjustable crossflow velocities from 5-50 m/s. The spray propagation during the injection process was measured with high-speed shadowgraphy. Two main parameters are introduced to describe the crossflow stability. The location of the intensity center represents the global spray deflection. The second parameter is the ratio between the areas of high and low optical spray density to express the spray "blow-out" under crossflow conditions. Five different injectors were investigated at injection pressures between 100 bar and 170 bar to determine their stability and behavior under crossflow conditions. The results show a clear dependence of the spray propagation on crossflow velocities. With increasing injection pressure the stability against crossflow is increasing. Furthermore, the injectors show different behavior at the same conditions due to their different nozzle designs.
Created from Fastlane, Scopus look-up

Correlating Gasoline Spray Propagation in Constant Volume Chamber and Optically Accessible Engines - Welß, Richard; Seeger, Jan; Deinhard, Bianca; Wensing, Michael (COMODIA 2017 Int. Conference, 2017)

Effect of superheated fuel on air entrainment under GDI-relevant boundary conditions measured with FPIV - Bornschlegel, Sebastian; Welß, Richard; Durst, Alexander; Conrad, Chris; Wensing, Michael; Jestrovic, Stevan (19th International Symposium on the Application of Laser and Imaging Techniques to Fluid Mechanics, 2018)
Fluorescent particle image velocimetry (FPIV) is used to examine the flow field around a single hole experimental injector under superheated and non-superheated conditions. The experimental injector is designed to match the behavior of a multi hole spray, that is common in modern gasoline direct injecting (GDI) engines. By its single hole design it eliminates the influence of jet-to-jet interaction and allows the isolated investigation of flashboiling effects on fuel sprays. Those effects occur, when fuel transits its boiling-curve during injection, leading to rapid evaporation at nozzle outlet. The air movement around the spray jet generally is found to be subdivided into three regions: In the displacement zone, air is pushed aside by the propagating spray front and its stagnation pressure. It is a function of spray front wid th, and spray front density. In this zone, the main momentum transfer with the surrounding air takes place, accelerating the captured air to spray velocity. Recirculation around the spray front takes place due to the pressure difference between the dynamic pressure of the spray front where the air is initially at rest, and the wake of the spray front where the air moves with spray velocity. It is therefore closely linked to air displacement. The stationary air entrainment equals the mass flow of air that is carried away with the stationary spray. Hence it is a function of the fuel-air ratio and the velocity in the spray. Flashboiling has different impact on those three air flow regimes. Both displacement and recirculation are increased significantly as, due to the evaporation of fuel, the spray front becomes wider and denser. Stationary air entrainment is increased too, but the effect is less pronounced, since the evaporating fuel replaces air in the spray jet and therefore partly counters the increase in spray volume, which leads to a moderately increased transport of air with the spray. It can be assumed that the reason for increased jet-to-jet interaction of flashboiling multi hole sprays, and the eventually resulting spray collapse, is not found in an significantly increased stationary air entrainment but rather in an overlap of the displacement zones of the individual jets and the resulting asymmetrical recirculation
Keywords: FPIV; Gasoline Spray; Superheated Injection; flashboiling

Indirect detector for ultra-high-speed X-ray micro-imaging with increased sensitivity to near-ultraviolet scintillator emission - Lukić, Bratislav; Rack, Alexander; Helfen, Lukas; Foster, Daniel J.; Ershov, Alexey; Welß, Richard; François, Stéphane; Rochet, Xavier (Journal of Synchrotron Radiation, 2024)
Ultra-high-speed synchrotron-based hard X-ray (i.e. above 10 keV) imaging is gaining a growing interest in a number of scientific domains for tracking non-repeatable dynamic phenomena at spatio-temporal microscales. This work describes an optimized indirect X-ray imaging microscope designed to achieve high performance at micrometre pixel size and megahertz acquisition speed. The entire detector optical arrangement has an improved sensitivity within the near-ultraviolet (NUV) part of the emitted spectrum (i.e. 310-430 nm wavelength). When combined with a single-crystal fast-decay scintillator, such as LYSO:Ce (Lu2-xYxSiO5:Ce), it exploits the potential of the NUV light-emitting scintillators. The indirect arrangement of the detector makes it suitable for high-dose applications that require high-energy illumination. This allows for synchrotron single-bunch hard X-ray imaging to be performed with improved true spatial resolution, as herein exemplified through pulsed wire explosion and superheated near-nozzle gasoline injection experiments at a pixel size of 3.2 μm, acquisition rates up to 1.4 MHz and effective exposure time down to 60 ps.
CRIS-Team Scopus Importer:2024-09-13
Keywords: high-speed imaging; indirect X-ray detectors; micro-imaging; polychromatic radiation

LIF Laser Scanning to Investigate Different Spray Characteristics and its Effect on the Mixture Formation in an DISI Engine - Welß, Richard; Bornschlegel, Sebastian; Wensing, Michael (ICLASS 2015, 13th International Conference on Liquid Atomization and Spray Systems, Tainan, 2015, 2015)
In DISI engines spray distribution and atomization directly influence the mixture formation, the quality of combustion and the resulting emissions. To investigate the mixture distribution in optically accessible gasoline engines, the measurement procedure laser lightsheet scanning (LSS) has been developed. The LSS method makes use of measuring the fuel distribution in multiple planes and is based on the laser induced fluorescence (LIF). Due to a tomographic evaluation it enables the detection of the spray propagation and mixture formation process, not only for a single plane, but for an extensive, three-dimensional part of the cylinder volume. Previous measurements to qualify the LSS method for its application are shortly summarized. New investigations of the spray formation carried out in a high pressure/high temperature injection chamber are shown where solely the influence of temperature and pressure on spray characteristics is investigated. Core of the contribution are investigations of spray and mixture formation inside an optical engine including the impact of incylinder charge motion. Three different gasoline injectors with multi-hole (typical for modern DISI engines) and colliding jet (new for gasoline direct injection) atomization were studied. The investigations were carried out at an operating point at 1200 rpm and 2.5 bar BMEP in an optically accessible single cylinder SI-engine. The injection process was recorded from start of injection at 220 °CA to 200 °CA BTDC, the ongoing mixture formation was recorded until 50 °CA BTDC. The results show the influence of different spray atomization on the mixture formation whereby the application of the LSS method allows a 3D-reconstruction of the fuel distribution during the spray and mixture formation process. To compare the homogenization process for the different injectors a uniformity index is used, that summarizes the mixture homogeneity reached in a certain crankangle position in one single value. The results show an equivalent homogenization level reached by the new developed twinjet injectors compared to the stock multi-hole injectors and demonstrate the potential of further development of the colliding jet atomization for direct injection gasoline engines. <br
Keywords: Automotive sprays; colliding jet atomization; laser induced fluorescence; laser diagnostics; optical engine

LIF Laser Scanning with pent roof illumination to Investigate Mixture Distribution in IC Engines with limited Optical Access - Welß, Richard; Wensing, Michael (18th International Symposium on the Application of Laser and Imaging Techniques to Fluid Mechanics, 2016)
Modern IC engines are realized with direct fuel injection, so the mixture formation takes place in the cylinder. Optical accessible engines allow a detailed investigation of the injection and mixture formation process. The measurement technique which is presented in this work is the tracer based Laser-induced fluorescence, which allows to quantify the air-fuel equivalence ratio in the engine. With this technique, only a single plane, which is illuminated by a lightsheet, is investigated. The new approach which is presented in this work is the Lightsheet scanning technique. To realize this approach the lightsheet is shifted laterally and several planes in the cylinder can be investigated. The focus in this work is to estimate the maximal cylinder which can be measured with this principle. Additionally, this idea is combined with a modified optical setup for the lightsheet forming to illuminate the pentroof through the glass ring without using a piston window. Different optical setups are studied to realize the best possible illumination of the pentroof. The chosen setup which was used finally is combined with the lightsheet scanning setup and used for the experiments. To align the optical setup fast and reliable to the different measurement planes, all relevant parts, lenses, mirror and camera, are mounted on electrically driven linear stages. The engine measurement results show the successful application of the developed method. In detail, two engine operating points are investigated and only the water temperature is varied. The method enables the reconstruction of any cross-sections, so that the spray targeting during the injection is shown in detail and differences between the two operating points are identified. The quality and progress of the mixture formation is evaluated by the uniformity index, which is calculated from every recorded plane. Additionally, the air-fuel ratio is also averaged over every plane and displayed over the crank angle to verify the results.<br
Keywords: tracer-LIF; Lightsheet Scanning; LSS; DISI engine; spray targeting; mixture formation

LIF Laser Scanning zur Untersuchung der Gemischbildung in Motoren mit reduziertem optischen Zugang - Welß, Richard; Bornschlegel, Sebastian; Heldmann, Markus; Wensing, Michael; Mederer, Thomas (Motorische Verbrennung – Aktuelle Probleme und moderne Lösungsansätze (XII. Tagung), 2016)

Mixture formation in DISI Engines investigated for conventional multi-hole and colliding-jet injectors by a new LIF technique - Welß, Richard; Mederer, Thomas; Heldmann, Markus; Wensing, Michael; et al. (THIESEL 2014 Conference on Thermo- and Fluid Dynamic Processes in Direct Injection Engines, 2014)

The influence of superheated injection on liquid and gaseous flow field of an experimental single-hole gasoline direct injection injector - Bornschlegel, Sebastian; Conrad, Chris; Durst, Alexander; Welß, Richard; Wensing, Michael; Olbinado, Margie; Helfen, Lukas; Baumbach, Tilo (International Journal of Engine Research, 2019)
In modern gasoline direct injection engines, the fuel is (partially) superheated for a significant proportion of the time during operation. This means that the vapour pressure of the fuel, or at least of many of its components, is higher than the ambient pressure inside the engine during injection. If the excess fuel enthalpy cannot be removed by evaporation at the free surface of the spray, the liquid phase boiling creates new surfaces. This phenomenon is known as flash boiling. Flash-boiling atomization produces smaller droplets and can therefore be beneficial as an additional atomization mechanism. Furthermore, it can reduce the penetration depth of a spray, although it also decreases the stability of fuel sprays. This is manifested in undesired targeting changes, that is, spray contraction due to jet-to-jet interaction. In extreme cases, a complete spray collapse can occur, where a multi-hole or hollow-cone spray contracts towards the spray axis and forms a jet-like structure that increases penetration depth. To understand the relationship between flash-boiling atomization and targeting changes, flash boiling was investigated with a single-hole generic injector without jet-to-jet interaction. In addition to macroscopic spray parameters, this study also focused on the flow field of the spray itself measured using laser Doppler anemometry, as well as the spray-induced flow field of the surrounding gas phase measured using fluorescent particle image velocimetry. The results show a strong radial expansion of the jet directly after nozzle exit, caused by internal flash boiling. It is shown that this expansion is caused by a zone of expanding fuel vapour in the centre of the spray. As a result, the displacement of air after injector opening as well as at the front of the spray is significantly increased, causing a decrease in spray front velocity and penetration depth. The stationary air entrainment, however, is only moderately increased as is the total amount of captured air, since the fuel vapour displaces air in the spray.
CRIS-Team Scopus Importer:2019-07-09
Keywords: flash boiling; fluorescent particle image velocimetry; Fuel spray; gasoline direct injection; optical metrology; phase Doppler anemometry; superheated fuel; X-ray phase contrast velocimetry